Protons Enhance Conductivities in Lithium Halide Hydroxide/Lithium Oxyhalide Solid Electrolytes by Forming Rotating Hydroxy Groups. Issue 3 (4th December 2017) - Song, Ah‐Young; Xiao, Yiran; Turcheniuk, Kostiantyn; Upadhya, Punith; Ramanujapuram, Anirudh; Benson, Jim; Magasinski, Alexandre; Olguin, Marco; Meda, Lamartine; Borodin, Oleg; Yushin, Gleb
Abstract: Li‐halide hydroxides (Li2 OHX) and Li‐oxyhalides (Li3 OX) have emerged as new classes of low‐cost, lightweight solid state electrolytes (SSE) showing promising Li‐ion conductivities. The similarity in the lattice parameters between them, careless synthesis, and insufficient rigor in characterization often lead to erroneous interpretations of their compositions. Finally, moisture remaining in the synthesis or cell assembling environment and variability in the equivalent circuit models additionally contribute to significant errors in their properties. Thus, there remains a controversy about the real values of Li‐ion conductivities in such SSEs. Here an ultra‐fast synthesis and comprehensive material characterization is utilized to report on the ionic conductivities of contaminant‐free Li2+xOH1−x Cl (x=0‐0.7), and Li2 OHBr not exceeding 10 ‐4 S cm ‐1 at 110 °C. Using powerful combination of experimental and numerical approaches, it is demonstrated that the presence of H in these SSEs yields significantly higher Li + ‐ionic conductivity. Born‐Oppenheimer molecular dynamics simulations show excellent agreement with experimental results and reveal an unexpected mechanism for faster Li + transport. It involves rotation of a short OH‐group in SSEs, which opens lower‐energy pathways for the formation of Frenkel defects and highly‐correlated Li + jumps. These findings will reduce the existing confusions and show new avenues for tuning SSE compositions for further improved Li‐ion conductivities. Abstract : Ultrafast and well‐controlled synthesis, comprehensive material characterization techniques, and a combination of experimental and modeling efforts reveal a significant impact of protons on the ionic conductivities of low‐cost lithium halide hydroxide/lithium oxyhalide solid state electrolytes (SSEs). Born–Oppenheimer molecular dynamics simulations revealed the link between OH ‐ group and Li + transport, which resembles rotating doors in buildings.